Emerging Technologies as a Support for Proprioceptive Rehabilitation: a Scoping Review - Trujillo Colón, Uziel; Hernández Hernández, José Luis; De La Cruz Gámez, Eduardo; Maldonado Astudillo, Rayma Ireri; Salazar, Ricardo (Revista Mexicana de Ingenieria Biomedica, 2025)
Proprioceptive training encompasses interventions aimed at enhancing proprioceptive function to improve motor function performance. Three types of interventions are considered: Movement Training (MT); Somatosensory Stimulation Training (SST), and Force Reproduction Training (FRT). This study analyzes the potential of emerging technologies, such as exoskeletons, mechanical devices, Artificial Intelligence (AI), Virtual Reality (VR), the Internet of Things (IoT), and sensors, highlighting their application in proprioceptive therapies, with particular emphasis on MT, SST, and FRT. A total of 107 articles published in scientific journals were reviewed, of which 30 complied with inclusion criteria: 1) Implementation of proprioceptive intervention therapy; 2) use of technology; 3) publication after 2019, and 4) written in the English language. Of the studies analyzed, 43 % employed AI, indicating its increasing adoption, while IoT was the least utilized technology, with only 3 %. It is concluded that emerging technologies plays a crucial role in proprioceptive rehabilitation by enabling the analysis of data before and after surgical procedures, real-time pattern assessment, and the classification of sensory signals. Moreover, it offers alternatives to traditional measurement methods.